Clinical analysis of adult-onset spinocerebellar ataxias in Thailand - Pairoj Boonkongchuen (2018)
Background: Non-ataxic symptoms of spinocerebellar ataxias (SCAs) vary widely and often overlap with various types of SCAs. Duration and severity of the disease and genetic background may play a role in such phenotypic diversity. We conducted the study in order to study clinical characteristics of common SCAs in Thailand and the factors that may influence their phenotypes.Methods: 131 (49.43%) out of 265 Thai ataxia families with cerebellar degeneration had positive tests for SCA1, SCA2, Machado-Joseph disease (MJD) or SCA6. The study evaluated 83 available families including SCA1 (21 patients), SCA2 (15), MJD (39) and SCA6 (8). Comparisons of frequency of each non-ataxic sign among different SCA subtypes were analysed. Multivariate logistic regression analyses were undertaken to analyze parameters in association with disease severity and size of CAG repeat.Results: Mean ages at onset were not different among patients with different SCAs (40.31 ± 11.33 years, mean ± SD). Surprisingly, SCA6 patients often had age at onset and phenotypes indistinguishable from SCA1, SCA2 and MJD. Frequencies of ophthalmoparesis, nystagmus, hyperreflexia and areflexia were significantly different among the common SCAs, whilst frequency of slow saccade was not. In contrast to Caucasian patients, parkinsonism, dystonia, dementia, and facial fasciculation were uncommon in Thai patients. Multivariate logistic regression analysis demonstrated that ophthalmoparesis (p < 0.001) and sensory impairment (p = 0.025) were associated with the severity of the disease.Conclusions: We described clinical characteristics of the 4 most common SCAs in Thailand accounting for almost 90% of familial spinocerebellar ataxias. There were some different observations compared to Caucasian patients including earlier age at onset of SCA6 and the paucity of extrapyramidal features, cognitive impairment and facial fasciculation. Severity of the disease, size of the pathological CAG repeat allele, genetic background and somatic heterogeneity of pathological alleles may influence clinical expressions of these common SCAs. © 2014 Boonkongchuen et al.; licensee BioMed Central Ltd.